Combination cryotherapy and intralesional corticosteroid versus steroid monotherapy in the treatment of keloids. (21st November 2022) - Cohen, Alexa J.; Talasila, Sahithi; Lazarevic, Bojan; Banner, Lauren; Gleason, Laura; Malkani, Kabir; Uitto, Jouni; Nikbakht, Neda
Abstract: Background: Keloids are common and have significant negative effects on quality of life. There is a need for more effective treatment approaches for keloids. Aims: We investigated treatment outcomes of intralesional triamcinolone acetonide (IL TAC) compared with combination IL TAC and cryotherapy, including changes in pruritus, pain, and keloid size. Patients/Methods: We performed a prospective study of patients referred to one provider who treated patients with combination therapy and compared them to a historic control cohort treated with IL TAC alone. All patients were seen at Thomas Jefferson University between 2019 and 2021. Patient demographics, location of keloids, and inciting events were recorded. Pruritus and pain scores were self‐reported by patients using a 10‐point Likert scale administered as standard of care. Changes in keloid size were denoted as "No change, " "up to 50% decrease, " "more than 50% decrease, " and "completely flattened." Results: While both treatments produced a significant reduction in mean pruritus and pain scores, there was no difference between the two treatment groups ( p = 0.3933 and p = 0.2123, respectively). A greater percentage of keloids in the combination therapy group had a post‐treatment size difference greater than 50% compared with those in the IL TAC only treatment group ( p = 0.0021). In the subgroup of pubic keloids, all lesions treated with combination IL TAC and cryotherapy responded remarkably well to treatment. Conclusions: While both IL TAC and IL TAC with cryotherapy were effective at reducing pruritus and pain, combination therapy was more effective in reducing keloid size, specifically for pubic keloids.